Managing change expert solutions to everyday challenges. (Boston, Mass. : Harvard Business Press, 2009)
In order to remain competitive in increasingly aggressive markets managers must adopt a positive attitude towards change. Successful managers know how to embrace change with an open mind and use it as a stimulus for new ideas, enthusiasm and progress.
Includes bibliographical references.
Description based on print version record.
Keywords: Organizational change -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books